A high-speed and high-efficiency imaging polarimeter based on ferroelectric liquid crystal retarders: Design and test. (16th February 2021) - Guo, Jing; Ren, Deqing; Zhu, Yongtian; Zhang, Xi
Abstract: Polarimeters play a key role in investigating solar magnetic fields. In this paper, a High speed and high efficiency Imaging POlarimeter (HIPO) is proposed based on a pair of ferroelectric liquid crystal retarders (FLCs), with the ultimate goal of measuring magnetic fields of prominences and filaments from the ground. A unique feature of the HIPO is that it enables high cadence polarization measurements covering a wide field of view (FOV); the modulation frequency of the HIPO is able to achieve ∼100 Hz, which greatly suppresses the seeing-induced crosstalk, and the maximum FOV can reach 62 ″ × 525 ″ . Additionally, FLC retardances under low and high states were calibrated individually and found to have a slight discrepancy, which is neglected in most works. Based on FLC calibration results, an optimization was performed using a constrained nonlinear minimization approach to obtain the maximum polarimetric efficiency. Specifically, optimized efficiencies of the Stokes Q, U, and V are well balanced and determined as (ξ Q, ξ U, ξ V ) = (0.5957, 0.5534, 0.5777), yielding a total efficiency of 0.9974. Their practical efficiencies are measured as (ξ Q ′, ξ U ′, ξ V ′) = (0.5934, 0.5385, 0.5747), slightly below the optimized values but still resulting in a high total efficiency of 0.9861. The HIPO shows advantages in terms of modulation frequency and polarimetric efficiency compared with most other representative ground-based solar polarimeters. In the observations, measurement accuracy is found to be better than 2.7 × 10 −3 by evaluating full Stokes Hα polarimetry results of the chromosphere. This work lays a foundation for the development of high-speed and high-accuracy polarimeters for our next-generation solar instruments.